O’ZBEKISTONDA TARQALGAN QUERCUS L TURKUMI VAKILLARI, ULARNING TARQALISHI VA AHAMIYATI (Ta'limning zamonaviy transformatsiyasi, 2024)
Анатация. В данной диссертации описываются представители отряда Quercus L, широко распространенные в Узбекистане, их распространение на местном уровне, их значение в природе и в народном хозяйстве.Annotation. This thesis describes the representatives of the order Quercus L, widespread in Uzbekistan, their distribution in the local, their importance in nature and in the national economy.